1991
DOI: 10.1002/j.1552-4604.1991.tb03718.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Fluconazole Metabolism by Rifampin: In Vivo Study in Humans

Abstract: The effects of rifampin on the pharmacokinetics of fluconazole were analyzed in an open-label, placebo-controlled, parallel study. Sixteen healthy male volunteers, randomized into two groups, received 200 mg of oral fluconazole on days 1 and 22. On days 8 through 27, group I received oral rifampin, 600 mg/d, and group II received placebo. Fluconazole in serum was analyzed by HPLC. On days 1 and 22, respectively, the AUC (micrograms.hr/mL) (mean +/- SD) was 160.5 +/- 19.5 and 124 +/- 22.2 in group I, 152 +/- 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Unlike ketoconazole, fluconazole is excreted mainly unchanged in the urine and so its elimination is not as markedly induced by rifampicin. Nevertheless, Apseloff et al (1991) have found a 19% decrease in the half-life of fluconazole, with no change in AUC, in 16 healthy male volunteers who received fluconazole on days 1 and 22 and rifampicin on days 8 to 27. The same workers have also suggested an increased dosage of fluconazole for the treatment of concomitant fungal infections in tuberculosis patients receiving rifampicin.…”
Section: Fluconazolementioning
confidence: 93%
“…Unlike ketoconazole, fluconazole is excreted mainly unchanged in the urine and so its elimination is not as markedly induced by rifampicin. Nevertheless, Apseloff et al (1991) have found a 19% decrease in the half-life of fluconazole, with no change in AUC, in 16 healthy male volunteers who received fluconazole on days 1 and 22 and rifampicin on days 8 to 27. The same workers have also suggested an increased dosage of fluconazole for the treatment of concomitant fungal infections in tuberculosis patients receiving rifampicin.…”
Section: Fluconazolementioning
confidence: 93%
“…Concomitant administration of rifampicin (and possibly rifabutin) with ketoconazole, itraconazole and, to a lesser extent, fluconazole, increase the metabolic clearance and decrease the AVC of the azoles; therapeutic failures of fungal infection have been reported (Apseloff et al 1991;Brass et al 1982;Doble et al 1988;Tucker et al 1992). Presumably, because ketoconazole is a substrate for CYP3A4 (table 11), rifampicin and other inducers increase ketoconazole metabolism.…”
Section: Rifampicin and Rifabutinmentioning
confidence: 99%
“…Posaconazole is primarily metabolised via UGT pathways (phase II enzymes), and therefore it is likely that induction of UGT pathways and CYP3A4 by phenytoin contributed to the interaction 137 . Although fluconazole undergoes little CYP‐mediated metabolism, drugs such as rifampin and its derivatives can accelerate its biotransformation, which significantly reduces its systemic exposure 160 …”
mentioning
confidence: 99%